Quercetin inhibits the biological activity of endometrial cancer by regulating autophagy: A network pharmacology analysis and cellular experimental validation - Lingchen Yang; Hongwei Ma (Journal of Functional Foods)
To investigate the effects of quercetin (Que) on the improvement of endometrial cancer (EC) and the relative associated mechanisms. Network pharmacology was used to analyze the correlation between Que. and EC. Ishikawa and HEC-1 A cell lines were used as research models in the present study. The cell lines were divided into the following groups: Normal, lentivirus (LV)-negative control (NC), Que., Que. + LV-activating transcription factor 5 (ATF5)-RNA interference (RNAi) and Que. + LV-ATF5-RNAi+mTOR agonist. Cell Counting Kit-8 and flow cytometry assays were used to evaluate cell proliferation and apoptosis; cell invasive and migratory abilities were assessed by Transwell and wound healing assays, respectively; the observation of the cell ultrastructure was performed by transmission electron microscopy; the relative protein expressions were measured by the western blot assay. Depending on results, Que. exhibited antitumor effects by stimulating autophagy via regulating the ATF5/JUN/PI3K/AKT/mTOR pathway in EC.